Extending the 4I organizational learning mModel: Information sources, foraging processes and tools - Tracy A. Jenkin (Administrative Sciences, 2013)
The continued importance of organizational learning has recently led to several calls for further developing the theory. This article addresses these calls by extending Crossan, Lane and White's (1999) 4I model to include a fifth process, information foraging, and a fourth level, the tool. The resulting 5I organizational learning model can be generalized to a number of learning contexts, especially those that involve understanding and making sense of data and information. Given the need for organizations to both innovate and increase productivity, and the volumes of data and information that are available to support both, the 5I model addresses an important organizational issue.
Keywords: 350; organizational learning; knowledge management; information foraging; information sources; supporting tools